KONSELING PENINGKATAN KUALITAS TIDUR PADA ANAK USIA 1-3 TAHUN MELALUI PIJAT DAN AROMATERAPI LAVENDER - Astutik, Indri; Handayani, Ririn; Iman Sari, Asri (LPPM Universitas dr. Soebandi, 2025)
Children aged 1–3 years are in a critical phase of growth and development, yet they often face sleep-related problems that can interfere with their overall development. This community service activity aims to improve understanding of how to enhance sleep quality in children aged 1–3 years through massage and aromatherapy. The method used was educational counseling conducted over one month, from May 1 to May 30, 2025, involving 30 participants. After the counseling sessions and sleep quality assessments using a questionnaire, the results showed that 16 children (53.4%) had good sleep quality, and 14 children (46.6%) had moderate sleep quality. In conclusion, this community service activity demonstrates that providing education to mothers of toddlers about massage and lavender aromatherapy can have a positive impact on improving sleep quality in children aged 1–3 years. This activity serves as an initial step in efforts to improve sleep quality through an educational approach and effective communication between healthcare providers and the community, and is expected to support sustainable improvements in sleep quality for children aged 1–3 years.